Polygamy from Quraish Shihab’s View in the Tafsir Al-Mishbah - Syamsuddin Syamsuddin; Zainal Abidin; Syahabuddin Syahabuddin (State Institute for Islamic Studies Palu, 2021)
This paper aims to find out the method used by Quraish and the factors that influenced his interpretation of polygamy in the Tafsir of Al-Mishbah. This research is a literature research using Arkoun's hermeneutic approach in analyzing the Quraish interpretation of Polygamy in his Tafsir. Data collection was carried out by citing and analyzing relevant literature on the issue discussed, then reviewing and concluding it. The results of this study indicate that polygamy is pictured as a small emergency exit that can only be conducted in emergency situation. The method used by Quraish Shihab in his interpretation of polygamy is the tahlili method, and the approach is more dominantly contextual. Likewise, the factores that influenced his interpretation include his social settings, schools of thought, and such figures such as Al-Biqai, Muh. Abduh, Tabataba'i, and Al-Farmawy.